Closed Reduction of an Acute Volar Dislocation of the Distal Radio-Ulnar Joint by a Modified Technique - Samuel Larrivée; Graeme Matthewson; Laurie Barron (Case Reports in Orthopedics)
There is scarce literature describing treatment of volar dislocation of the distal radio-ulnar joint (DRUJ). Irreducible dislocation is usually treated surgically. We present the case of a 37-year-old male with acute right wrist pain and loss of pronation. A diagnosis of volar DRUJ dislocation was made. Reduction using conventional technique was unsuccessful. A second attempt was successful by applying pressure over the interosseous membrane of the forearm and manipulating the ulnar head. At three weeks, the patient had minimal pain, a stable DRUJ, and near complete range of motion. This modified technique for reduction of a locked anterior DRUJ dislocation can be used to avoid an unnecessary surgical intervention.